Scale validation to measure digital competence among older adults - Pinzón Zamora, Jhoana Victoria (2026)
The increasing participation of older adults in digital environments underscores the need for valid instruments to assess their digital competence. This study aimed to develop and validate a scale to measure self-perceived digital communication competence among older adults, grounded in the European Digital Competence Framework for Citizens (DigComp). A quantitative, cross-sectional design was employed, using non-probabilistic purposive sampling. Content validity was assessed through expert judgment (Aiken’s V > .80), followed by a pilot study with 17 participants. Subsequently, the initial 15-item version of the instrument was administered to 381 adults aged 60 years and older residing in Cajeme, Sonora, Mexico, in March 2025. Based on the psychometric analyses conducted, a final validated version consisting of 10 items was obtained after removing five items that exhibited cross-loadings and conceptual ambiguity, which hindered clear differentiation between dimensions. The Likert-type scale was examined using confirmatory factor analysis, yielding satisfactory fit indices (CFI = .97, TLI = .96, RMSEA = .06), along with high internal consistency (α = .92; ω = .93). The results indicate that the instrument demonstrates adequate psychometric properties, supporting its relevance as a tool for assessment and for the design of educational interventions aimed at promoting digital inclusion among older adults. Further research is recommended to replicate the study in other contexts in order to strengthen its external validity.